KEWAJIBAN LIBYA TERHADAP INDONESIA TERKAIT TUMPAHNYA MINYAK MENTAH YANG MENCEMARI PERAIRAN INDONESIA - Yosua Yanko (LPPM Universitas Ekasakti Padang, 2022)
Legal research on the Libya’s obligations to Indonesia regarding the crude oil spilled that polluted Indonesia’s sea, which is created liability based on international agreements regarding marine pollution because the Libya has ratified the international agreement. Therefore Libya must comply with the provisions of the United Nations Convention on the Law Of the Sea 1982, International Convention on Civil Liability for Oil Pollution Damage 1969, Stockholm Declaration and Rio de Janeiro Declaration 1992. The purpose of this research is to find out the liability carried out by the Libya due to the crude oil spilled that polluted Indonesian’s sea due to an accident with the MV Sinar Kapuas from Singapore. Normative methods used in this study focus on the strict liability principle and sea international treaties, including the United Nations Convention on the Law Of the Sea 1982, International Convention on Civil Liability for Oil Pollution Damage 1969, Stockholm Declaration and Rio de Janeiro Declaration 1992. Marine pollution by crude oil carried out by the MT Alyarmouk from Libya created a liability which is determined as strict liability by the International Convention on Civil Liability for Oil Pollution Damage 1969.